PENGARUH PROFITABILITAS, AUDIT FIRM SIZE, LEVERAGE DAN UKURAN PERUSAHAAN TERHADAP VOLUNTARY DISCLOSURE (Studi Empiris Pada Perusahaan Sektor Perbankan yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2023) - Riansyah, Raisa Wahida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
Voluntary discloure is the proactive provision of additional information bycompanies, exceeding mandatory regulatory requirements, to enhancetransparency, reduce information asymmetry, and support stakeholders in makingwell-informed decisions. The purpose of this research is to determine the influenceof profitability, audit firm size, leverage and firm size on voluntary disclosure onbanking sector listed on the Indonesia Stock Exchange (IDX) during 2021-2023.Samples were determined using purposive sampling. Testing this hypothesis usesmultiple linearregression analysis conducted with the help of SPSS 26. Profitabilityhas a signigicance level of 0,006 < 0,05, then Ha is accepted, which means thatProfitability has an effect on Voluntary Disclosure. Audit Firm Size has asignificance level of 0,032 < 0,05, then Ha is accepted, which means that AuditFirm Size has an Effect on Voluntary Disclosure. Leverage has a significance levelof 0,147 > 0,05, then H0 is accepted, which means that Leverage has no effect onVoluntary Disclosure. Firm Size has a significance level of 0,000 < 0,05, then Hais accepted, which means that Firm Size has an effect on Voluntary Disclosure.Keyword : Profitability, Audit Firm Size, Leverage And Firm Size On VoluntaryDisclosure